Critical measurement issues in the assessment of social media influence on body image. (March 2022) - Jarman, Hannah K.; McLean, Siân A.; Griffiths, Scott; Teague, Samantha J.; Rodgers, Rachel F.; Paxton, Susan J.; Austen, Emma; Harris, Emily; Steward, Trevor; Shatte, Adrian; Khanh-Dao Le, Long; Anwar, Tarique; et al.
Highlights: The rise of social media has led to a flood of research examining its impact on body image. This review outlines the range of approaches used to measure social media use. Most are insufficient at capturing the complexity of social media experiences. A critical perspective is presented, highlighting the gaps within the literature. Future recommendations include combining methods and broadening measurement indices. Abstract: Progress towards understanding how social media impacts body image hinges on the use of appropriate measurement tools and methodologies. This review provides an overview of common (qualitative, self-report survey, lab-based experiments) and emerging (momentary assessment, computational) methodological approaches to the exploration of the impact of social media on body image. The potential of these methodologies is detailed, with examples illustrating current use as well as opportunities for expansion. A key theme from our review is that each methodology has provided insights for the body image research field, yet is insufficient in isolation to fully capture the nuance and complexity of social media experiences. Thus, in consideration of gaps in methodology, we emphasise the need for big picture thinking that leverages and combines the strengths of each of these methodologies to yield a more comprehensive, nuanced, and robust picture of the positive and negative impacts of social media.